Acute Mountain Sickness Is Associated With a High Ratio of Endogenous Testosterone to Estradiol After High-Altitude Exposure at 3,700 m in Young Chinese Men - Ding, Xiao-Han; Wang, Yanchun; Cui, Bin; Qin, Jun; Zhang, Ji-Hang; Rao, Rong-Sheng; Yu, Shi-Yong; Zhao, Xiao-Hui; Huang, Lan (Frontiers in Physiology, 2019)
Background: A large proportion of populations suffer from acute mountain sickness (AMS) after exposure at high altitude. AMS is closely related with age and gender implying that the sex hormones may play critical roles in AMS. Our observational study aimed to identify the association between the endogenous testosterone (T), estradiol (E2) and AMS. Methods: A total of 113 subjects were recruited in 2012. The participants were evaluated at 500 m and after acute (one day) and short-term (seven days) high-altitude exposure at 3700 m. The subjects also completed a case report form questionnaire and underwent blood pressure measurements and an echocardiography examination. The red blood cell (RBC) count, Hb concentration ([Hb]), hematocrit (HCT), E2, T and erythropoietin (EPO) were measured. Results: Upon acute high-altitude exposure, E2 and EPO were significantly lower in AMS+ group, and T/E2and stroke volume were higher. On the first day, AMS score correlated positively with the T/E2 ratio while it negatively correlated with E2. After seven days at 3700 m, the AMS+ subjects had higher erythropoietic parameters: EPO, T and T/E2 were significantly higher in the AMS+ group. [Hb], RBC count, HCT, EPO, T and T/E2 were also correlated with AMS score. EPO, HCT and the RBC count were also correlated with T/E2. Regression analyses indicated that T/E2 significantly correlated to AMS score and T/E2 on the first day was an independent predictor for AMS on the 7th day. Conclusions: AMS was correlated with T/E2 ratio and EPO. After short-term exposure, higher T/E2 may contribute to AMS together with EPO via erythropoiesis. Furthermore, T/E2 level at high altitude in the early stage was an independent predictor for AMS in the latter stage.